Higher Platelet Count Mostly in Normal Range is Associated with First Episode of Peritonitis Risk in Incident Peritoneal Dialysis Patients - Jing Yu; Hongjian Ye; Yi Li; Shun Hua; Jiaqi Liu; Hongyu Li; Yating Wang; Haiping Mao (Kidney & Blood Pressure Research)
Background. Platelets play parts in infection and immune processes. However, the association between platelet count and the risk of peritoneal dialysis-associated peritonitis is unclear. Methods. This was a retrospective, observational, single-center cohort study. A Cox regression analysis was used to evaluate the independent association of platelet count with the occurrence of first PD-associated peritonitis. Models were adjusted for gender, age, BMI, cardiovascular disease, diabetes mellitus, white blood cell count, neutrophil-lymphocyte ratio, hemoglobin level, albumin level, potassium level, and anti-platelet medication usage. Results. A total of 2374 patients were enrolled in this study (59% men; mean age 47.40 ± 12.12). The average platelet count was 229.30±82.12 x 109/L. 467 (20%) patients suffered from PD-associated peritonitis at least once. In the multivariable model, the adjusted hazard ratios (HRs) for quartiles 2, 3 and 4 versus quartile 1 were 1.428 (95% CI 1.060-1.924, P=0.019), 1.663 (95% CI 1.240-2.229, P<0.001) and 1.843 (95% CI 1.363-2.492, P<0.001) with baseline data. A nonlinear relationship between platelet count and first PD-associated peritonitis was observed. Further, the association between platelet and first PD-associated peritonitis was significant in the patients with hypokalemia (P for interaction=0.040). Conclusion. In PD patients, elevated platelet counts were significantly associated with an increased risk of the first onset of PD-associated peritonitis.